Two Distinct Effects of cGMP on Cytosolic Ca2+ Concentration of Rat Pancreatic β-Cells - Tomohisa Ishikawa; Yukiko Kaneko; Fumi Sugino; Koichi Nakayama (Elsevier, 2003)
The present study investigated the effects of cGMP on cytosolic Ca2+ concentration ([Ca2+]c) of isolated rat pancreatic β-cells. In the presence of 7.0 mM glucose, NOC 7, a nitric oxide (NO) donor, caused an increase in [Ca2+]c of the β-cells, which was abolished by the soluble guanylate cyclase inhibitor ODQ. Similar [Ca2+]c elevation was evoked by 8-bromo-cGMP. The [Ca2+]c elevating responses to NOC 7 and 8-bromo-cGMP were abolished by nicardipine or in a Ca2+-free medium, but were not affected by thapsigargin, suggesting that they are produced by the Ca2+ influx through L-type voltage-operated Ca2+ channels. In contrast, NOC 7 and 8-bromo-cGMP decreased the [Ca2+]c when it was raised in advance by the elevation of external K+ concentration to 30 mM or by 4-aminopyridine. The pretreatment with thapsigargin almost abolished the [Ca2+]c reduction induced by the agents, suggesting that the action is likely to be primarily attributable to an acceleration of the Ca2+ sequestration into the endoplasmic reticulum. These results suggest that cGMP has two distinct effects on the [Ca2+]c of rat pancreatic β-cells: a facilitation of the Ca2+ influx through L-type voltage-operated Ca2+ channels and an acceleration of the Ca2+ sequestration in the endoplasmic reticulum.